The Live Experiences of Mothers of Children with Disability in Karbala City a Qualitative Study - Esraa Shaker Saeed; Zainab Abidzaid Al-Hadrawy; Alaq Hameed Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
Holding a toddler with disabilities at domestic causes severe issues and conflicts for all circle of relatives participants to exceptional levels. However, because of their stronger emotional connection, mothers are most at risk from the issues of worrying for children with disabilities. The goal of the present observe changed into therefore to explore the dwelling revel in of mothers of kids with disabilities in karbala. Methods: In this qualitative phenomenological research, the statistical pattern consisted of mothers of children with disabilities living in karbala, from which 20 topics had been selected via selective sampling and analyzed the use of in-depth interviews. Sampling proceeded to the factor of facts saturation and, on the same time as interview. Results: The findings of this have a look at confirmed that key issues protected dwelling reports of mothers of kids with disabilities, specifically interpersonal relationships and social stories. The revel in of mothers with disabilities has additionally been proven to have eight sub-issues feelings of shame, loss of assets, maternal sacrifice, problem for the future, feelings of shame for different kids, isolation, lack of socio-financial assist and stigmatization Conclusion: The findings of this study have proven that there are numerous and varied difficulties and boundaries faced by means of mothers of kids with disabilities. The burden of stress on mothers can be minimized and their resilience better by using taking an expansion of steps concerning man or woman interventions and social aid.